Impact of international and local conditions on sovereign bond spreads: International evidence - Selma Izadi (Borsa Istanbul Review, 2018)
This paper examines the effect of international and domestic factors on the sovereign bond spreads for 22 developed countries in North America, Europe and Pacific Rim regions. First, for all the regions the impact of global factors on the sovereign bond spreads is more intense than regional factors. Second, the findings confirm that for the bond spreads of each region over its domestic government bonds, the countries’ local fundamentals are better determinants of the spreads compared to the spread over US government bonds as a safe haven. Third, the influence of worldwide factors in the Eurozone compared to other regions bond spreads is less. Fourth, the relationship of the market sentiment and the investor risk aversion with the sovereign bond spreads of all regions is positive. Equity market volatility plays significant role in yield speads in international bond markets.